Tax Disputes Resolution In Nigeria: Going Beyound The Traditional Court And Administrative Resolution System - Anyebe, Peter Ademu (Advances in Social Sciences Research Journal, 2020)
It is the requirement of law that tax is paid. Therefore, the discharge of tax obligation in Nigeria is not by choice. In the process of the tax authorities who are authorized under the law to collect taxes from tax payers, disputes arise. The paper reveals that in its bid to lessen the incidents of tax evasion in Nigeria, the Federal Government carried out a major reform in its tax regime. Thus, the Tax Appeal Tribunal (TAT) was established to ensure fairness and transparency of the tax system through a quick and efficient method of dispensing justice. Appeal from there lies to the Federal High Court on point of law. However, there is the unresolved problem of the constitutionality of TAT in its powers and jurisdiction in resolving tax disputes with Federal High Court (FHC). Furthermore, the paper reveals that tax disputes are not arbitrable under Nigerian law. It is the argument of this paper that although the courts are recognized as the most visible dispute arbiter, it is not always the most effective or efficient method. Therefore, it is further the argument of this paper that Nigeria’s tax objection procedures as governed by statutory rules should incorporate Alternative Dispute Resolution mechanism as practiced in other jurisdictions. The paper recommends that the necessary amendments should be made to enable TAT and FHC at their levels to encourage the use of early dispute resolution (EDR) and alternative dispute resolution (ADR), particularly mediation in the settlement of tax disputes brought before them. The introduction of VAIDS (Voluntary Assets and Income Declaration Scheme) by the Federal Government of Nigeria is in line with global best practices on non-disclosure of informal and declaration of assets. The paper concludes among others that Nigeria, as a country cannot operate in isolation, hence the introduction of ADR in its tax dispute resolution processes should be imminent and mandatory.